Classification system for nanotechnology-enabled health products with both scientific and regulatory application - Rodríguez-Gómez, Francisco D.; Penon, Oriol; Monferrer, Dominique; Rivera-Gil, Pilar (Frontiers in Medicine, 2023)
The lack of specific regulatory guidelines for nanotechnology-enabled health products (NHPs) is hampering development and patient access to these innovative technologies. Namely, there is an urgent need for harmonized regulatory definitions and classification systems that allow establishing a standardized framework for NHPs regulatory assessment. In this work, a novel classification system for NHPs is proposed. This classification can be applied for sorting nano-based innovations and regulatory guidelines according to the type of NHPs they address. Said methodology combines scientific and regulatory principles and it is based on the following criteria: principal mode of action, chemical composition, medical purpose and nanomanufacturing approach. This classification system could serve as a useful tool to sensor the state of the art of NHPs which is particularly useful for regulators to support strategy development of regulatory guidelines. Additionally, this tool would also allow manufacturers of NHPs to align their development plans with their applicable guidelines and standards and thus fulfill regulators expectations.